2021
DOI: 10.1007/s00213-021-05969-7
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias in individuals with depression and adverse childhood experiences: influence of the noradrenergic system?

Abstract: Rationale Major depressive disorder (MDD) is a severe mental disorder with affective, cognitive, and somatic symptoms. Mood congruent cognitive biases, including a negative attentional bias, are important for development, maintenance, and recurrence of depressive symptoms. MDD is associated with maladaptive changes in the biological stress systems such as dysregulations of central noradrenergic alpha2-receptors in the locus coeruleus-noradrenergic system, which can affect cognitive processes incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 106 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…By using an eye-tracking method, ample evidence has been repeatedly reported that MDD is associated with aberrant attentional bias during negative face recognition ( Lazarov et al, 2018 ; Klawohn et al, 2020 ; Kuehl et al, 2021 ). For instance, Klawohn et al (2020) found that the depressed group dwelled longer on sad faces than healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…By using an eye-tracking method, ample evidence has been repeatedly reported that MDD is associated with aberrant attentional bias during negative face recognition ( Lazarov et al, 2018 ; Klawohn et al, 2020 ; Kuehl et al, 2021 ). For instance, Klawohn et al (2020) found that the depressed group dwelled longer on sad faces than healthy people.…”
Section: Introductionmentioning
confidence: 99%